Through indigenous eyes: looking for indigenous services in Australian and New Zealand university libraries - Lilley S (Information Research)
Introduction. This paper reports on how indigenous services, collections and languages are represented on university library Websites in Australia and New Zealand. In an era of increased dependence on technology, it is critical that university libraries ensure that indigenous services, collections and languages are visible on their Website. Method. Websites of forty-eight university libraries were probed for information about the services, collections and facilities offered to indigenous students. Prior to commencing the search, a tool consisting of six factors was designed to evaluate each Website. Analysis. Using the tool, each Website was analysed and where matches were found, these were noted and each institution was awarded a score. Results There is considerable scope for improvement across the six factors. The Australian libraries scored much lower than their New Zealand counterparts. However, institutions from both countries displayed examples of best practice that would enhance Websites and improve services and resources for indigenous students. Conclusions . As indigenous student numbers continue to increase at universities in both countries, it is critical that libraries ensure that they have services, collections and facilities in place and easily identifiable on their Websites. Libraries that fail to include such information risk the danger of alienating indigenous students.
Keywords: Indigenous library and information services; Indigenisation; Māori; Aboriginal and Torres Strait Islander; 0806 Information Systems; 0807 Library and Information Studies